Model ADDIE Branch Dalam Pengembangan E-Learning Biologi - Tiara Putri Weldami; Relsas Yogica (Departement of Mathematics Education, 2023)
A teacher must choose an appropriate development model to develop e-learning. The goal is that e-learning has components that can accommodate good quality learning. One of the development models that can be used is the ADDIE model developed by Robert Maribe Branch, a Professor in the field of learning, design and technology. This research is a literature study. The aim is to review the ADDIE model for biology e-learning development. Data was collected, analyzed and synthesized from various sources such as articles, previous studies, reports and books. The data analysis technique is content analysis and is presented in a qualitative descriptive manner. The results of the analysis show that the ADDIE model has principles that are in line with the current characteristics of e-learning and biology learning. The stages in the ADDIE model navigate in detail the development of a systematic and structured biology e-learning